(untitled) (Scientific journal of the Fergana State University, 2024)
This scientific article reveals the classification of the genre of fantasy used in Khudoyberdi Tokhtabayev’s work "Riding the Yellow Giant". The main factor in the widespread use of the fantasy method in the work is the method of analysis of the effectiveness of the artistic text. It is scientifically based that the content-stagnant genres occupy an important place in literature. The relevance of research methods on this topic is evidenced by the emergence of new fantasy works and their adaptation to cinema, the increasing popularity of such literature, and as a result, the plot of the work written in the fantasy genre is based on the principle of adventure. As a conclusion of the research, it is proved that the classification of the fantasy genre used in the writer’s work is related to the content of all its features.